ANALYSIS OF BIBLIOMETRIC DATA ON STUDY OF THE CRITICAL THINKING PHENOMENON (UKRAINIAN-LANGUAGE GOOGLE SCHOLAR CONTENT, 2020-2023) - Habrusieva, Nataliia; Kryskov, Andrii; Aliluiko, Sergii (Physical and Mathematical Education, 2025)
Formulation of the problem. Modern information technologies open up new opportunities for research, including pedagogical one. Information about current trends in the development of a scientific problem can be obtained from the analysis of bibliometric data, access to which is now greatly facilitated by extensive scientometric databases (Web of Science, Scopus Google Scholar, etc.). Such information makes it possible to summarise preliminary results, identify current trends, emphases, specifics of the issues under study, and predict the prospects for future research. Formation of critical thinking is one of the main tasks of pedagogical process and modernisation of Ukrainian education. For the practical implementation of this task, an important step is to study the bibliometric data of recent publications on the subject. Materials and Methods. The article analyses the main bibliometric indicators of Ukrainian-language works that study the phenomenon of critical thinking (Google Scholar, 2020-2023). A comparative analysis with similar studies of Web of Science (2000-2021) is carried out. For the analysis of bibliometric sources from Google Scholar in conducting content analysis, we used Power BI Desktop, while Microsoft Excel and IBM® SPSS® Statistics were employed for statistical data analysis. Results. It is established that the share of critical thinking research by Ukrainian scientists is the largest in the educational sphere. Statistical processing of the documents obtained as a result of the search for “critical thinking” by the form of materials submission and the field of scientific research was carried out. An analysis of the number of citations of the received documents in specific years is carried out, which indicates the interest of readers in the developments of a certain direction. According to the content of the keywords, the groups indicating the peculiarities of the critical thinking study by Ukrainian scientists at the present stage and the directions of scientific research are allocated. The multidirectionality of research by Ukrainian educators is statistically substantiated. The main methods, approaches, techniques and technologies for the formation of critical thinking in recent years are outlined. The emphasis of modern pedagogical techniques for the development of critical thinking on the formation of media literacy and the use of information and communication technologies is determined. The negative factors that influence the formation of critical thinking, noted by Ukrainian scientists during the study period, are recorded. Conclusions. We see prospects for further research in utilizing the obtained results of bibliometric data analysis to refine the approaches to developing critical thinking in learners and applying them in pedagogical practice.